Modernization of Hydrological Services in Japan and Lessons for Developing Countries - World Bank (World Bank, Washington, DC, 2017)
River and basin management covers various factors, including disaster management, river water use, and conservation of the river environment. Any of these factors involves a number of intricately intertwined stakeholders who may have different needs. Over time, efforts to manage water-related disasters in Japan have led to the concept of integrated river basin management and to a mechanism allowing central management of river basins by river management authorities. These attempts to promote more advanced integrated management of river basins have provided the foundation of social and economic development in Japan today. The collected hydrological data and forecast information are used by river management authorities themselves and also delivered to municipalities, fire and police authorities, and the Self-Defense Forces in an effort to prevent disasters from occurring, assist residents in evacuating safely, and provide emergency response quickly. At present, hydrological information is used for operating and managing structures such as dams and water gates, monitoring unusual events during floods, and forecasting inundation. This is widely shared by local governments, which make decisions on evacuation orders and advisories; organizations that support disaster management efforts of local governments; government headquarters for disaster control, which are activated in case of large-scale disasters; organizations that operate lifeline utilities (e.g., electric power, gas) and traffic infrastructure (e.g., expressway, railway); and mass media.